Analisis Pengaruh Tingkat Pemahaman Dan Kendala Yang Di Hadapi Penumpang Terhadap Pemahaman Penggunaan Web Check-In Pada Maskapai Citilink: Studi Kasus: Bandara Internasional Adi Soemarmo Solo - Afifa Agustus; Fryda Fatmayati (MAMEN: Jurnal Manajemen, 2022)
To reduce crowds during a pandemics, the airlines convenience prospective passengers to check-in via web check-in, but due to lack of socialization from the airline, passengers are still confused and hesitant to use it due to lack of knowledge about web check-in Citilink airline at Adi Soemarmo Ineternational Airport, Solo. Many passengers still do manual check-in. The purpose of this study determine how much the analysis of the influence level of understanding and constraints on passengers on understanding of web check-in Citilink Airlines at Adi Soemarmo International Airport. This  Research uses a quantitative method. The population is all Citilink passengers at the Adi Soemarmo Solo International Airport from September to October. The technique in this study is a purposive sampling, this data processing use a questionnaire, and the data processing use the SPSS 21 software program. The data analysis used validity test, reliability test, multiple linear regression, T test, F test, and coefficient of determination (R2). The results of the analysis on the F is F count > F table, there is an influence on the level of understanding and obstacles faced by passengers on understanding of web check-in on Citilink airlines at Adi Soemarmo Solo International Airport. And the result of the coefficient of determination (R2) of 51,1% means the variable understanding of web check-in can explained by the variable level of understanding and obstacles faced by passengers, while 48,9% is explained by other variables.